2010
DOI: 10.1902/jop.2010.090310
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless Tobacco Use and Periodontal Health in a Rural Male Population

Abstract: Background-Despite the reported effects of smokeless tobacco (ST) on the periodontium and high prevalence of ST use in rural populations and in men, studies on this specific topic are limited. The purpose of this cross-sectional investigation is to evaluate the periodontal health status of male ST users from a rural population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 40 publications
6
52
2
Order By: Relevance
“…It is well-documented that clinical periodontal parameters among CS and STU have increased percentage of deep probing depths, a higher clinical attachment loss, and increased alveolar bone loss compared with NTU 16,17 ; however, to our information from the literature, the present study is the first study to compare clinical and radiographic parameters around dental implants and proinflammatory cytokine levels among CS (Group-1), STU (Group-2), and NTU (Group-3). The purpose of the present study is supported on the hypothesis that periimplant clinical and radiographic inflammatory parameters are worse in CS and STU compared with nontobacco users.…”
Section: Discussionmentioning
confidence: 81%
“…It is well-documented that clinical periodontal parameters among CS and STU have increased percentage of deep probing depths, a higher clinical attachment loss, and increased alveolar bone loss compared with NTU 16,17 ; however, to our information from the literature, the present study is the first study to compare clinical and radiographic parameters around dental implants and proinflammatory cytokine levels among CS (Group-1), STU (Group-2), and NTU (Group-3). The purpose of the present study is supported on the hypothesis that periimplant clinical and radiographic inflammatory parameters are worse in CS and STU compared with nontobacco users.…”
Section: Discussionmentioning
confidence: 81%
“…These differences for the various parameters of gingival REC were significant for all regions except for sites with REC of ≥ 5 mm in maxillary, premolar and molar sites. Whilst earlier studies showed that ST use was associated with increased gingival REC mainly at the site of tobacco placement , the findings of the present study showed that ST use may be associated with a generalized increase in gingival REC and that the habit can result in an increased prevalence, extent and severity of REC that may not be as localized as previously considered. Monten et al .…”
Section: Discussionmentioning
confidence: 93%
“…Tobacco use is considered a modifiable risk factor, and diabetes is a systemic risk factor . Tobacco use in the form of cigarette, cigar, or pipe smoking, as well as smokeless tobacco use, causes gum recession and bone loss . Diabetes impacts blood vessels and inflammatory processes that increase the risk for periodontal disease, especially when diabetes is not well‐controlled …”
mentioning
confidence: 99%